Sulfuryl Chloride Promoted gem-Dichlorination–Dehydrochlorination in Alkyl Benzothiazinylacetates: Synthesis of the Skeleton of Trichochrome Pigments - Jangir, Ravi; Gadre, Smita R.; Argade, Narshinha P. (Synthesis, 2015)
Chemo- and stereoselective total synthesis of the basic trichochrome skeleton is described starting from o-aminothiophenol and maleic anhydride in very good overall yield. The process involves the synthesis of the corresponding 1,4-benzothiazin-2-ylacetates followed by their sulfuryl chloride induced dihalogenation–dehydrohalogenation and a second condensation with o-aminothiophenol as key steps.
Keywords: o-aminothiophenol; maleic anhydride; halogenation; condensations; trichochrome framework